Citrate enhances resilience to chronic variable stress and has antidepressant properties in female mice - Sahlloul, Yasmin (2024)
Major depressive disorder (MDD) is a prevalent and disabling psychiatric disorder with high prevalence among women. Available methods of treatment, including pharmacotherapy and psychotherapy, do not provide high effectiveness and are accompanied by adverse side effects. In recent years, nonpharmaceutical interventions such as exercise and healthy dietary modifications, have been suggested as novel ways of treating MDD yielding promising and non-toxic results. Exercise exerts its beneficial effects by mediating the upregulation of brain-derived neurotrophic factor (BDNF) and promoting the release of circulatory factors, including the metabolite citrate. Here we have studied the prophylactic and antidepressant effects of citrate in female mice subjected to chronic variable stress (CVS). Two different paradigms were applied, the pretreatment and post-treatment paradigms, to assess the prophylactic and antidepressant effect of citrate respectively. In the pretreatment paradigm, citrate administration began 5 days prior to and through the CVS paradigm whereas treatment commenced after the induction of depressive-like behavior in the post-treatment paradigm. Results show that citrate exerts prophylactic effect and is able to rescue depressive-like behavior and potentially ameliorate anxiety-like behavior. Upon investigating the molecular pathway of citrate’s therapeutic effect, the BDNF/TrkB pathway and epigenetic modifications in the hippocampus and nucleus accumbens (NAc) were not modulated following citrate treatment. However, citrate differentially modulated autophagy-related proteins in these regions suggest that citrate mediates its effect through the regulation of autophagy. These findings highlight the potential of citrate as a novel therapeutic and prophylactic approach for MDD in females.